Hospital Value-Based Purchasing and Trauma-Certified Hospital Performance. Issue 1 (January 2019) - Spaulding, Aaron; Hamadi, Hanadi; Martinez, Luis; Martin, Timothy; Purnell, Justin M.; Zhao, Mei
ABSTRACT: Introduction: Hospital Value-Based Purchasing (HVBP) is an initiative that rewards acute-care hospitals with incentive payments for the quality of care they provide. A hospital's trauma certification has the potential to influence HVBP scores as attaining the certification provides indication of the service quality offered by the hospital. As such, this study focuses on hospitals' level of trauma certification attainment through the American College of Surgeons and whether this certification is associated with greater HVBP. Methods: A retrospective review of the 2015 HVBP database, 2015 Area Health Resources Files (AHRF) database, and the 2015 American Hospital Association (AHA) database is utilized, and propensity score matching was employed to determine the association between level of trauma certification and scores on HVBP dimensions. Results: Results reveal trauma certification is associated with lower HVBP domain scores when compared to hospitals without trauma certification. In addition, hospitals with a greater degree of trauma specialization were associated with lower total performance score and efficiency domain scores. Conclusions: Although payers attempt to connect hospital reimbursements with quality and outcomes, unintended consequences may occur. In response to these results, HVBP risk adjustment and scoring methods should receive further scrutiny.